User experiences of automated dispensing cabinets in hospital wards: recommendations for improved workflows and patient safety - Korhonen, Julia; Viitanen, Johanna; Ahtiainen, Hanne; Tolonen, Hanna M.; Sandell, Annukka; Lahdenne, Pekka (Finnish Journal of eHealth and eWelfare, 2024)
Medical treatment in hospitals is a complex process in which errors can lead to patient harm and adverse events and additional costs to the healthcare system. In Finland, automated dispensing cabinets have been introduced to an increasing extent, with one of their objectives being to reduce medication errors and thus improve patient safety and streamline the work of the staff. Practical challenges in using them have been identified, especially from the perspective of nurses. This user experience study aimed to improve the work processes of the professionals and the use of automated dispensing cabinets integrated into patient information systems in hospital wards without endangering patient safety. The qualitative data was collected in spring 2023 by interviewing nurses (N=6), ward pharmacists (N=3) and pharmacy assistants (N=2). The findings were validated and improvement suggestions were produced in a multidisciplinary workshop with about 30 participants. As a result, seven different themes related to the use of the automated dispensing cabinets were identified: interruption of work and queueing, slowness of the work process, lack of space, human errors and lack of competence, technical challenges, deviation from the medication dispensing process and other challenging features of the automated dispensing cabinets. Based on these, development suggestions were created, which can be categorized into three themes: resources and facilities, orientation and guidance, and medicine storage solutions and work processes. Further research is needed on the user experiences of automated dispensing cabinets integrated into patient information systems in other wards, as well as the possibilities of unit dose dispensing and storing medicines partly also outside the automated dispensing cabinets.